2012
DOI: 10.1016/j.neuroimage.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The Human Connectome Project: A data acquisition perspective

Abstract: The Human Connectome Project (HCP) is an ambitious 5-year effort to characterize brain connectivity and function and their variability in healthy adults. This review summarizes the data acquisition plans being implemented by a consortium of HCP investigators who will study a population of 1200 subjects (twins and their non-twin siblings) using multiple imaging modalities along with extensive behavioral and genetic data. The imaging modalities will include diffusion imaging (dMRI), resting-state fMRI (R-fMRI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
2,059
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,302 publications
(2,069 citation statements)
references
References 62 publications
7
2,059
1
2
Order By: Relevance
“…Although continued development of prospective methods will improve the way that future studies use structural imaging to study anatomy [see Zaitsev et al, 2015], development of such innovations is not applicable to a number of extremely valuable legacy datasets and to many other on‐going large‐scale data collection initiatives [e.g., ABIDE, ADHD‐200, ADNI, Betula, DLBS, FCON1000, HCP, HABS, NIMH adolescents, PNC, SLS; ADHD‐200‐Consortium, 2012; Biswal et al, 2010; Chan et al, 2014; Dagley et al, 2015; Di Martino et al, 2014; Giedd et al, 1999; Jack et al, 2008; Nilsson et al, 1997, 2004; Park et al, 2012; Satterthwaite et al, 2014; Schaie and Willis, 2010; Van Essen et al, 2012b, 2013]. While many studies have led efforts to correct the motion‐related bias in EPI, less work has demonstrated a suitable technique for mitigating the motion‐related bias on T1w imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although continued development of prospective methods will improve the way that future studies use structural imaging to study anatomy [see Zaitsev et al, 2015], development of such innovations is not applicable to a number of extremely valuable legacy datasets and to many other on‐going large‐scale data collection initiatives [e.g., ABIDE, ADHD‐200, ADNI, Betula, DLBS, FCON1000, HCP, HABS, NIMH adolescents, PNC, SLS; ADHD‐200‐Consortium, 2012; Biswal et al, 2010; Chan et al, 2014; Dagley et al, 2015; Di Martino et al, 2014; Giedd et al, 1999; Jack et al, 2008; Nilsson et al, 1997, 2004; Park et al, 2012; Satterthwaite et al, 2014; Schaie and Willis, 2010; Van Essen et al, 2012b, 2013]. While many studies have led efforts to correct the motion‐related bias in EPI, less work has demonstrated a suitable technique for mitigating the motion‐related bias on T1w imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset was acquired on a Siemens 3 T Skyra MRI scanner equipped with a 32‐channel phased‐array head coil and a customized SC72 gradient insert featuring a maximum gradient strength of 100 mT/m 36. A spin‐echo Stejskal–Tanner sequence measured two b ‐shells of about 1000 and 2500 s/mm 2 with 76 and 75 gradient directions, respectively, which together with their antipodal points are uniformly distributed on the sphere 37.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the Human Connectome Project (HCP) [4,5] is accumulating vast amounts of image data in order to accelerate our understanding of brain function. This and predecessor programs such as the Bioinformatics Research Network (BIRN) [6,7] have established medical imaging firmly in the realm of big-data-based science.…”
Section: Introductionmentioning
confidence: 99%